Organic acid profile of chestnut (Castanea sativa Mill.) as affected by hot air convective drying - Delgado, Teresa (2018)
The objective of the present work was to evaluate the effect of hot air convective drying on the organic acid profile of chestnut. An extractive method, with internal standard, followed by HPLC-UV was validated, allowing the quantification of malic, ascorbic, citric, and fumaric acids with good precision and accuracy. Fresh chestnuts presented differences between varieties. The thermal process caused equivalent losses of ascorbic acid on both varieties, but higher losses of malic acid in Longal. Furthermore, fumaric acid contents increased on both varieties. Therefore, hot air convective drying affected the organic acid composition of chestnut slices, and this effect was varietal dependent.